Quercetin inhibits cardiomyocyte apoptosis via Sirt3/SOD2/mitochondrial reactive oxygen species during myocardial ischemia–reperfusion injury - Da Xiong; Xin Wang; Haiyu Wang; Xia Chen; Hongrong Li; Yongwu Li; Minghua Zhong; Jingcheng Gao; Zicong Zhao; Wenjun Ren (Heliyon)
Background: Myocardial ischemia/reperfusion injury (MI/RI) can lead to impaired cardiac function. Quercetin (Que) has a positive effect and improves MI/RI. Sirtuin-3 (Sirt3) is a deacetylase that ameliorates oxidative stress and is associated with MI/RI. This study aimed to investigate the molecular mechanism by which Que protects cardiac function against MI/RI through the Sirt3 signaling pathway. Methods: We conducted experiments by constructing hypoxia/reoxygenation (H/R) cardiomyocytes and MI/RI rat models. H9C2 cells were transfected with siRNA-Sirt3. Cardiomyocyte apoptosis was examined by TUNEL and Western blotting. The oxidative stress index was also determined. Mitochondrial reactive oxygen species (ROS) activity assays, ATP assays and mitochondrial membrane potential assays were performed. Evans Blue/TTC staining was used to examine surviving myocardial tissue. Results: In the constructed H/R cells and MI/RI animal models, it was found that myocardial cell apoptosis increased (Bcl-2 expression was downregulated; Bax and cleaved caspase-3/8/9 expression were upregulated). In addition, oxidative stress levels increased (MDA levels increased; SOD, CAT, GSH-Px levels decreased), myocardial tissue was damaged (LDH, CK content increased), Sirt3 expression was downregulated, acetylation levels of superoxide dismutase 2 (SOD2) increased (AC-SOD2), and mitochondrial ROS increased. Que treatment alleviated the effects of MI/RI on cardiomyocytes and rats. Sirt3 expression and activity were upregulated, SOD2 acetylation was decreased, and mitochondrial ROS production was reduced by Que treatment. After Sirt3 was knocked down, we found that AC-SOD2 expression was upregulated and mitochondrial ROS were increased in H/R cardiomyocytes, further increased the degree of injury, while Que treatment attenuated the effect of Sirt3 knockdown on H/R cardiomyocytes. Conclusion: Que inhibits cardiomyocyte apoptosis, reduces oxidative stress levels, protects mitochondrial function and prevents the impairment of cardiac function during MI/RI via the Sirt3/SOD2/mitochondrial ROS pathway.